2019
DOI: 10.1039/c8nr09802f
|View full text |Cite
|
Sign up to set email alerts
|

A new tool to attack biofilms: driving magnetic iron-oxide nanoparticles to disrupt the matrix

Abstract: Removing robust MRSA biofilms using magnetic nanoparticles (MNPs) under AC and DC magnetic field is demonstrated. Despite being non-toxic to planktonic bacteria, MNPs can bring damage to the extracellular matrix of biofilms and remove them from surfaces without inducing bacterial resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 15 publications
2
57
0
Order By: Relevance
“…Considering all three tested sizes (8, 11, and 70 nm), although the application of AC fields allowed a local heating of the biofilms, DC fields showed to be the most effective strategy to break the EPS matrix and kill the bacteria. A 4.71 log 10 reduction was achieved in biofilm bacteria after the treatment with 30 mg ml −1 of 11 nm NPs, under DC magnetic field (Li J. et al, 2019).…”
Section: Magnetic Fieldmentioning
confidence: 97%
See 1 more Smart Citation
“…Considering all three tested sizes (8, 11, and 70 nm), although the application of AC fields allowed a local heating of the biofilms, DC fields showed to be the most effective strategy to break the EPS matrix and kill the bacteria. A 4.71 log 10 reduction was achieved in biofilm bacteria after the treatment with 30 mg ml −1 of 11 nm NPs, under DC magnetic field (Li J. et al, 2019).…”
Section: Magnetic Fieldmentioning
confidence: 97%
“…Several studies showed that, besides the good biocompatibility and low cytotoxicity, MNPs can be controlled and concentrated close to a target, through the application of an external magnetic field. This allows a deeper penetration into the biofilm and interferes in the organization of the matrix (Subbiahdoss et al, 2012;Bandara et al, 2015;Li J. et al, 2019;Quan et al, 2019). Consequently, possible elimination of the target biofilm is achieved through its breakup, along with cell detachment.…”
Section: Magnetic Fieldmentioning
confidence: 99%
“…Therefore, interference with this effective anti-biofilm agent have been published but the route for derivation is to change the periphery so it acts more as a delivery system rather than a chemical agent. [33][34][35] Research has been conducted into the role of iron and other metal in the production of biofilms, and it has been determined that iron plays a very important role with iron scavengers inhibiting biofilm formation also. [36][37][38]…”
Section: Biological Properties Analysismentioning
confidence: 99%
“…26,27,31 In addition, iron oxide nanoparticles have been shown to be an effective tool for the disruption or inactivation of biolms, increasing drug permeability and causing pathogens detachment. [32][33][34] Magnetic nanoparticles have been proposed as antimicrobial agents against several pathogenic microorganisms, such as bacteria, viruses and fungi. 24,27,35,36 A promising approach relies on the use of aerosol formulations containing SPIONs (nanomagnetosols) in order to improve the targeting of the aerosol toward a specic region of lungs.…”
Section: Introductionmentioning
confidence: 99%